Determination of spin-label orientation within the myosin head. - Fajer, P G (1994)
Current methods of analyzing EPR spectra of spin-labeled muscle fibers allow the determination of spin-label orientation within the fiber, rather than the orientation of the myosin head itself. In order to describe the orientational distribution of spin labeled myosin heads within the muscle fibers, the orientation of the spin label within the myosin head must be known. The iodoacetamide label orientation in the myosin head was determined to be (16.8 degrees, 28.3 degrees, 4.2 degrees) or (16.6 degrees, 72.0 degrees, 4.3 degrees). These Eulerian angles were obtained from the analysis of EPR spectra of fibers decorated with labeled myosin heads in the absence of ATP, with the assumption that the head's tilt angle is 40 degrees, as observed in a recent EM study [Pollard, T., Bhandari, D., Maupin, P., Wachsstock, D., Weeds, A. & Zot, H. (1993) Biophys. J. 64, 454-471]. Knowledge of spin-label orientation will allow for quantitative determination of myosin head orientation in the various states of the contractile cycle.